PERLINDUNGAN HUKUM MITRA DRIVER SHOPEEFOOD DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN ATAS KERUGIAN AKIBAT KELALAIAN RESTORAN - Muhamad Rival Maulana; Miko Aditiya Suharto (Jurnal Ilmiah Advokasi, 2026)
This study examines the legal protection of ShopeeFood driver-partners who suffer losses due to customer complaints arising from restaurant negligence. In practice, drivers are often subjected to sanctions such as rating reductions, incentive deductions, and even partnership termination, despite the absence of fault on their part. This research aims to analyze the form of legal protection provided by the platform and to identify the legal remedies available for drivers to defend their rights. The study employs an empirical juridical method with a socio-legal approach, utilizing field surveys and literature review. The findings indicate that the existing legal protection remains largely formalistic and ineffective in practice, particularly due to inadequate complaint-handling and appeal mechanisms that fail to ensure fairness for drivers. This situation reflects an imbalance of power among the platform, restaurants, and driver-partners within the partnership framework. Therefore, it is necessary to strengthen partnership agreement clauses, enhance transparency in evaluation systems, and improve oversight of restaurant responsibilities to ensure more equitable and proportional legal protection.Keywords: Legal Protection; Driver-Partners; Customer Complaints; Fairness; Digital Platforms